Oral Microbiome Dysbiosis as a Risk Factor for Stroke: A Comprehensive Review - Georgy Leonov; Diana Salikhova; Antonina Starodubova; Andrey Vasilyev; Oleg Makhnach; Timur Fatkhudinov; Dmitry Goldshtein (Microorganisms, 2024)
Stroke represents a significant global health burden, with a substantial impact on mortality, morbidity, and long-term disability. The examination of stroke biomarkers, particularly the oral microbiome, offers a promising avenue for advancing our understanding of the factors that contribute to stroke risk and for developing strategies to mitigate that risk. This review highlights the significant correlations between oral diseases, such as periodontitis and caries, and the onset of stroke. Periodontal pathogens within the oral microbiome have been identified as a contributing factor in the exacerbation of risk factors for stroke, including obesity, dyslipidemia, atherosclerosis, hypertension, and endothelial dysfunction. The alteration of the oral microbiome may contribute to these conditions, emphasizing the vital role of oral health in the prevention of cardiovascular disease. The integration of dental and medical health practices represents a promising avenue for enhancing stroke prevention efforts and improving patient outcomes.